Variability in date palm fruits (Phoenix dactylifera L.) collected from Kachchh region of Gujarat (Indian Journal of Arid Horticulture, 2020)
Date palm (Phoenix dactylifera L.; family- Arecaceae) is one of the most important fruit trees for semi arid and hot arid regions of the country. It is an ancient fruit and believed to be indigenous to countries around Persian Gulf. Date palm groves in coastal region of Kachchh from Anjar to Mandvi have developed naturally through seeds, which probably brought by Turk settlers, traders, gardeners and Haj pilgrims. The seedlings are very old in Kachchh region and some new systematic plantations of date palm have also been developed either through suckers or tissue culture plants of cv. Barhee. Moreover, seedling populations of date palm are not found in other parts of country. The ripe fruits (doka or khalal) are used for fresh consumption and processing. Every part of the date palm plant is useful since its history of cultivation and utilization. Dried fruit pulp is used for flavoring the bakery products. Date palm leaves are also used for making handicraft items viz., broom, hand-fan, mat, rope etc. Date is nutritious fruit having high calorific value in the form of sugar, minerals and vitamins (Zaid, 1999; Singh, 2018). It has high market potential for the production of soft dates (pind khajoor) and dry dates (chhuhara). However, processing is very less in our country. Presently, India imports about 3,11,575 MT dates every year from Gulf countries to meet out the domestic requirement.
Keywords: domestic; Gulf; Phoenix dactylifera L.; family- Arecaceae